"MORINGA OLEIFERA IN THE TREATMENT OF OSTEOPOROSIS: A COMPREHENSIVE REVIEW OF MECHANISMS, EFFICACY, AND FUTURE DIRECTIONS" - Naruboyina Vasavi; L.S. Jyothika; Y. Sai Charan Teja; K. Somasekhar Reddy; D. Yamini Kalyani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Osteoporosis is a pressing health concern characterized by diminished bone density and increased susceptibility to fractures, particularly among the elderly. The condition poses significant challenges due to its silent progression and substantial impact on quality of life and healthcare systems. Addressing osteoporosis requires effective prevention and treatment strategies. Moringa oleifera, commonly known as the "drumstick tree," has garnered attention for its potential therapeutic effects in managing osteoporosis. This review outlines the accumulating evidence suggesting that Moringa oleifera may offer promising avenues for osteoporosis management. Notably, Moringa oleifera contains a plethora of bioactive components, including vitamins, minerals, flavonoids, and glucosinolates, which contribute to its medicinal properties. Exploration of the mechanisms of action underlying Moringa oleifera’s effects on bone health reveals its potential to promote bone formation, inhibit bone resorption, and exert anti-inflammatory and antioxidant effects. Preclinical studies have demonstrated encouraging results, showing improvements in bone mineral density, bone architecture, and biomarkers of bone turnover. Furthermore, clinical evidence supports the efficacy and safety of Moringa oleifera supplementation in osteoporosis patients. However, further research is warranted to elucidate optimal dosing regimens, evaluate long-term outcomes, and address potential confounding factors. In conclusion, this review highlights the potential of Moringa oleifera as a natural adjunctive therapy for osteoporosis. By synthesizing current knowledge on its bioactive components, mechanisms of action, preclinical and clinical evidence, and future research directions, this review aims to contribute to the growing understanding of Moringa oleifera’s role in osteoporosis management